Malebranche, theological figure, being 2 - Badiou, Alain (The Seminars of Alain Badiou, 2019)
Alain Badiou offers a tour de force encounter with a lesser-known seventeenth-century philosopher and theologian, Nicolas Malebranche, a contemporary and peer of Spinoza and Leibniz. The seminar is at once a record of Badiou's thought at a key moment and a lively interrogation of Malebranche's key text, the Treatise on Nature and Grace.